Search for light pseudoscalar boson pairs produced from Higgs boson decays using the 4τ and 2μ2τ final states in proton-proton collisions at $$ \sqrt{s}=13 $$ TeV - Chekhovsky,V; Hayrapetyan,A; Makarenko,V; Tumasyan,A; Adam,W; Andrejkovic,JW; Benato,L; Bergauer,T; Chatterjee,S; Damanakis,K; Dragicevic,M; Hussain,PS; et al. (Journal of High Energy Physics, 2026)
A bstract A search for a pair of light pseudoscalar bosons (a 1 ) produced in the decay of the 125 GeV Higgs boson is presented. The analysis examines decay modes where one a 1 decays into a pair of tau leptons and the other decays into either another pair of tau leptons or a pair of muons. The a 1 boson mass probed in this study ranges from 4 to 15 GeV. The data sample was recorded by the CMS experiment in proton-proton collisions at a center-of-mass energy of 13 TeV and corresponds to an integrated luminosity of 138 fb − 1 . No excess above standard model (SM) expectations is observed. The study combines the 4τ and 2μ2τ channels to set upper limits at 95% confidence level (CL) on the product of the Higgs boson production cross section and the branching fraction to the 4τ final state, relative to the Higgs boson production cross section predicted by the SM. In this interpretation, the a 1 boson is assumed to have Yukawa-like couplings to fermions, with coupling strengths proportional to the respective fermion masses. The observed (expected) upper limits range between 0.007 (0.011) and 0.079 (0.066) across the mass range considered. The results are also interpreted in the context of models with two Higgs doublets and an additional complex singlet field (2HD+S). The tightest constraints are obtained for the Type III 2HD+S mod